The printed book - Aldis, Harry Gidney (The Cambridge manuals of science and literature, 1916)
The advent of printing.--The spread of the art.--The fifteenth-century book.--The scholar-printers of the sixteenth century.--English books, 1500-1800.--The modern book.--The construction of a book.--Illustrations.--Bookbinding and bookbindings.--The handling and mishandling of books.--Bibliography (p. [144]-148)--Index.